International marketing and export management. - Albaum, Gerald S., 1933-; Duerr, Edwin, ....- (New York : Prentice Hall, 2008)
Chapter 1 - International Marketing and Exporting Chapter 2 - Bases of International Marketing Chapter 3 - The International Environment: Culture, Economic Forces, Political/Legal, and Competition Chapter 4 - Export Market Selection: Definition and Strategies Chapter 5 - Information for International Market(ing) Decisions Chapter 6 - Market Entry Strategies Chapter 7 - Export Entry Modes Chapter 8 - Nonexport Entry Modes Chapter 9 - Product Decisions Chapter 10 - Pricing Decisions Chapter 11 - Financing and Methods of Payment Chapter 12 - Promotion and Marketing Communication Chapter 13 - Handling Export Orders and Supply Chain Management Chapter 14 - Organization of International Marketing Activities
Keywords: Export; Internationale marketing